Accuracy Assessment of 3D-Printed Surgical Guide with Custom-Made Sleeve versus Freehand Technique for Zygomatic Implant Placement: A Randomized Clinical Trial - Moawad Abdelfattah, Abdelfattah; Abd Raboo, Bahaa El-Din; Elakher Mohamed, Mohamed Abd (Journal of Neonatal Surgery, 2025)
Background: Zygomatic implants offer a graftless solution for severe maxillary atrophy. However, the accuracy of computer-guided versus freehand placement remains debated. This randomized clinical trial aimed to compare accuracy of these two techniques using CT-based deviation analysis. Methods: Eight patients requiring zygomatic implants were randomized into two equal groups: computer-guided (n = 4) and freehand placement (n = 4), with a total of 16 implants. Radiographic accuracy was assessed by comparing planned and actual implant positions using postoperative CT superimposition. Deviations were quantified in linear (mediolateral and anteroposterior) and angular dimensions. Statistical analysis was conducted using independent t-tests and Mann-Whitney U tests (significance level α = 0.05). Results: The guided group demonstrated significantly higher radiographic accuracy compared to the freehand group. Linear deviation in the mediolateral plane was 49.66 ± 1.87 mm versus 53.47 ± 1.70 mm (p < 0.001), and in the anteroposterior plane was 49.78 ± 14.61 mm versus 21.84 ± 4.54 mm (p < 0.001). Angular deviation was significantly reduced in the guided group (5.17° ± 2.31°) compared to the freehand group (11.80° ± 8.48°, p = 0.050). Conclusion: Computer-guided placement of zygomatic implants significantly improves the accuracy over the freehand approach. These findings support the use of guided techniques in cases requiring precise maxillary rehabilitation, particularly in anatomically complex or severely atrophic maxillae.